2017
DOI: 10.1007/s00204-017-2083-x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal toxicity of deoxynivalenol is limited by Lactobacillus rhamnosus RC007 in pig jejunum explants

Abstract: Probiotics have been explored to stimulate gut health in weaned pigs, when they started to consume solid diet where mycotoxins could be present. The aim of this study was to evaluate the effect of Lactobacillus rhamnosus RC007 on the intestinal toxicity of deoxynivalenol (DON) in an ex vivo model. Jejunal explants, obtained from 5-week-old crossbred castrated male piglets, were kept as control, exposed for 3 h to 10 μM DON, incubated for 4 h with 10 CFU/mL L. rhamnosus, or pre-incubated 1 h with 10 L. rhamnosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 52 publications
3
37
1
Order By: Relevance
“…DON derivatives (DON‐3‐glucoside, 15‐acetyldeoxynivalenol, and 3‐acetyldeoxynivalenol) are equally a safety concern for consumers (Vidal, Mengelers, Yang, De Saeger, & De Boevre, ). The potential of L. rhamnosus RC007 to eliminate intestinal toxicity caused by DON in an ex vivo porcine model has been reported in a recent study (Garcia et al., ), in which L. rhamnosus RC007 prevented DON‐related toxic effects on jejunal explants, including paracellular permeability, histological alterations, increased phosphorylation of MAP kinases p38 and p42/p44, and increased expression of pro‐inflammatory cytokines. In another study (Maidana, Gerez, Pinho, Garcia, & Bracarense, ), the oral exposure of DON to 24 days old piglets resulted in defects in histological and morphometric parameters of intestinal tissues, which included apical necrosis, villi atrophy, and a decrease in villi height.…”
Section: Protection Provided By Lab Against the Toxic Effects Of Mycomentioning
confidence: 79%
“…DON derivatives (DON‐3‐glucoside, 15‐acetyldeoxynivalenol, and 3‐acetyldeoxynivalenol) are equally a safety concern for consumers (Vidal, Mengelers, Yang, De Saeger, & De Boevre, ). The potential of L. rhamnosus RC007 to eliminate intestinal toxicity caused by DON in an ex vivo porcine model has been reported in a recent study (Garcia et al., ), in which L. rhamnosus RC007 prevented DON‐related toxic effects on jejunal explants, including paracellular permeability, histological alterations, increased phosphorylation of MAP kinases p38 and p42/p44, and increased expression of pro‐inflammatory cytokines. In another study (Maidana, Gerez, Pinho, Garcia, & Bracarense, ), the oral exposure of DON to 24 days old piglets resulted in defects in histological and morphometric parameters of intestinal tissues, which included apical necrosis, villi atrophy, and a decrease in villi height.…”
Section: Protection Provided By Lab Against the Toxic Effects Of Mycomentioning
confidence: 79%
“…García et al. (2018), Juodeikiene et al. (2018), Yang, Li, Duan, and Yang (2017), and Chlebicz and Śliżewska (2019) observed the effects of DON detoxification by Lactobacillus sp.…”
Section: Degradation Of Don By Microorganismsmentioning
confidence: 96%
“…Among the strains, L. plantarum achieved the best result (Zou et al, 2012). García et al (2018), Juodeikiene et al (2018), Yang, Li, Duan, and Yang (2017), and Chlebicz and Śliżewska (2019) observed the effects of DON detoxification by Lactobacillus sp. strains, Pediococcus pentosaceus strains, and metabolites Lactobacillus rhamnosus RC007 and Lactobacillus plantarum JM113.…”
Section: Lactic Acid Bacteriamentioning
confidence: 98%
See 2 more Smart Citations